Understanding Leadership from the Inside Out: Assessing Leadership Potential Using Constructive-Developmental Theory. (April 2014) - Helsing, Deborah; Howell, Annie
This article explores the value for the organization of assessing leaders' mental complexity using a measure of developmental stage known as the Subject–Object Interview. We first describe the existing literature that uses constructive-developmental theory to explore leadership, focusing particularly on Kegan's theory of Adult Development. We then describe our application of this theory to participants in a leadership development fellowship at the World Economic Forum. As in many organizational leadership contexts, the program makes "mental demands" on its participants to be predominately at Kegan's Self-Authoring stage of meaning making. Fellows' successes and struggles related to their developmental stage, although the nature of these relationships was not always straightforward. This finding underscores the importance of utilizing a developmental assessment that can provide rich and nuanced data as a tool for a leader's personal development, as well as for insight into leadership development programs and processes.